THE INFLUENCE OF THE RUSSIAN UKRAINIAN WAR ON GLOBAL AND DOMESTIC FOOD SUPPLY - MUDRAK, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Under fictitious pretexts, Russia has unleashed an unprovoked war against Ukraine that is spreading beyond our country. One of the most tragic consequences of this war is the intensification of the global problem of hunger. Ukraine and Russia are among the leading suppliers of food to the global market - they account for 25.4% of world wheat exports and 17.6% of coarse grain. Forecasts of declining exports of their grain products have provoked an unprecedented rise in global food prices. The critical dependence of the global food market on Ukrainian agri-food exports has formed in the segment of sunflower oil - Ukraine accounts for almost 50% of the relevant market. As Ukraine's share in the structure of global sunflower oil production is 30.6%, it is impossible to find a replacement in the short term. Together with the risks of sanctions restrictions on Russian exports, this led to an increase in world prices for sunflower oil from 1,700 to 2,250 dollars for 1 t. Many poor countries that are currently facing a catastrophic food shortage are buyers of Ukrainian grain products - until recently, Ukraine was the main supplier of wheat grain to Ethiopia, Lebanon and Pakistan. Ukraine has been a major supplier of corn grain to China - in 2021 it accounted for 78.3% of Chinese imports of these products. Blocking the export of Ukrainian corn threatens to reduce the number of pigs in China and reduce the production of relevant products.The resumption of Ukrainian agri-food exports in the previous volumes is possible only if the cessation of hostilities, the return of control over all ports and the unblocking of Azov and Black Sea civilian shipping. Because the possibilities of logistics of transport communications on land do not exceed 1 million tons of grain per month. There are grounds for restrained optimism about Ukraine's domestic food security on the following basis: the country has stocks of wheat, corn, sunflower oil, basic products for 3-5 years; according to various forecasts in Ukraine this year is expected to produce cereals and legumes, technical and other crops in sufficient quantities for domestic food supply; the forced sharp reduction in exports of Ukrainian grain products may lead to its redirection to the feeding of farm animals and increase meat production in areas where there is no fighting.
Keywords: war; food crisis; grain; reduction of exports; prices; poor countries; famine; domestic provision